Degradation of unassembled and damaged thylakoid proteins. (August 2001) - Adam, Z.; Ostersetzer, O.
Abstract : To study protein degradation in thylakoid membranes we identified, characterized and cloned thylakoid proteases, and then linked them to known proteolytic processes. Several families of chloroplast proteases were identified and characterized to different extents. FtsH, an ATP-dependent metalloprotease that belongs to the AAA-protein family, was found to be integral to the thylakoid membrane, facing the stroma. It is involved in both the degradation of unassembled subunits of membrane complexes, such as the Rieske Fe-S protein of the cytochrome complex, and the degradation of oxidatively damaged proteins such as the D1 protein of the photosystem II (PS II) reaction centre. Plant genomes contain multiple isomers of this protease but the functional significance of this multiplication is not clear yet. A second protease, the serine ATP-independent DegP, was found to be strongly associated with the luminal side of the thylakoid membrane. Although a specific role has not yet assigned for it, its location suggests that it can degrade luminal soluble proteins as well as luminally exposed regions of thylakoid membrane proteins.